Complementary impact of capabilities and brand orientation on SMBs performance - Ciunova-Shuleska, Anita; Osakwe, Christian Nedu; Palamidovska-Sterjadovska, Nikolina (Journal of Business Economics and Management, 2016)
The purpose of this study is to analyse the interrelationships among capabilities and brand orientation and their effect on performance of the small and medium-sized businesses. A data set of 181 effective responses is collected and Partial Least Squares was used. The main drivers of customer performance are brand orientation and adaptive and brand promotional capabilities, while financial performance is determined by brand promotional and e-marketing capabilities and by customer performance. Brand orientation directly influences adaptive and brand promotional capabilities, while e-marketing capability is positively influenced by brand promotional capability. SMBs operating in the developing economy context need to combine multiple capabilities and brand orientation with focus on building e-marketing capability to improve financial performance. This research study is one of the first in the South-eastern European context to offer evidence-based insights on the structural relations among multiple capabilities, brand orientation and the performance of SMBs.